Integrated transcriptome and 16S rDNA analyses reveal that acute heat stress induces intestinal damage in Gymnocypris eckloni - Duan, Yuting; Li, Hejiao; Li, Junting; Bai, Shuhao; Fu, Suxing; Zhou, Yinhua; Liu, Shidong; Li, Rundong; Liu, Haiping; Zhou, Chaowei; Lei, Luo (Frontiers in Marine Science, 2024)
Gymnocypris eckloni (G. eckloni), a cold-water economic fish, is widely cultivated in southwestern China. The increase in extreme summer weather conditions owing to global warming can significantly affect their survival and health. The fish intestine and its microbiota are closely associated with fish feeding and growth, nutritional metabolism, and immune defense. However, the mechanisms underlying the changes in the G. eckloni intestine and its microbiota under acute heat stress remain unknown. In this study, we investigated the effects of acute heat stress on the G. eckloni intestine employing histology, plasma biochemical indices, transcriptomics, and 16S rDNA sequencing. Histological analysis showed that acute heat stress induced significant morphological damage to the intestine, with microvilli detachment and mitochondrial abnormalities in the ultrastructure. Biochemical indicators associated with stress (reactive oxygen species and catalase), inflammation (interleukin-1β and tumor necrosis factor-α), and intestinal permeability (diamine oxidase and lipopolysaccharide) were significantly elevated after acute heat stress, indicating an intestinal inflammatory response and disruption of barrier function. Many DEGs were mined by transcriptomic analysis, with tfrc, pfkp, egln1 enriched in the HlF-1 signaling pathway, hsp70, hsp90aa1 and hspa4 enriched in the Antigen processing and presentation pathway, pmm1, pfkfb3 and hk1 enriched in the Fructose and mannose metabolism patyway. The HIF-1 signaling pathway is a crucial regulatory pathway during acute heat stress in the G. eckloni intestine, while significant downregulation of genes associated with adaptive immunity (mica, hla-dpa1, hla-dpb1, and hla-dqb2) suggested impaired immune function. Additionally, the composition of the intestinal microbiota was dominated by Aeromonas, Citrobacter, and Acinetobacter in the control group; but there was a significant decrease in the abundance of Citrobacter and Acinetobacter, and a significantly increased in Shewanella and Hafnia-Obesumbacterium after acute heat stress. Correlation analyses revealed that changes in the abundance of Hafnia-Obesumbacterium, Buttiauxella, and Pseudomonas were closely associated with changes in gene expression associated with stress, inflammation, and immunity. These results comprehensively demonstrate the adaptive mechanisms of the G. eckloni intestine in response to acutely high temperatures and provide a theoretical basis for the future advancement of artificial culture of cold-water fish.